2020
DOI: 10.3390/toxins12070440
|View full text |Cite
|
Sign up to set email alerts
|

Over 25 Years of Pediatric Botulinum Toxin Treatments: What Have We Learned from Injection Techniques, Doses, Dilutions, and Recovery of Repeated Injections?

Abstract: Botulinum toxin type A (BTXA) has been used for over 25 years in the management of pediatric lower and upper limb hypertonia, with the first reports in 1993. The most common indication is the injection of the triceps surae muscle for the correction of spastic equinus gait in children with cerebral palsy. The upper limb injection goals include improvements in function, better positioning of the arm, and facilitating the ease of care. Neurotoxin type A is the most widely used serotype in the pediatric po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 132 publications
1
24
1
2
Order By: Relevance
“…Based on animal and human data and clinical experience, BTX diffusion is likely to occur up to a distance of 4.5-5 cm from the injection site (to some extent, even into adjacent muscles). This depends on the dosage and volume injected (31) and on the muscle fiber structure and presence of spasticity (23). The hyperintense region's extent in our study in CP patients with muscle contractures was smaller than this maximum distance.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Based on animal and human data and clinical experience, BTX diffusion is likely to occur up to a distance of 4.5-5 cm from the injection site (to some extent, even into adjacent muscles). This depends on the dosage and volume injected (31) and on the muscle fiber structure and presence of spasticity (23). The hyperintense region's extent in our study in CP patients with muscle contractures was smaller than this maximum distance.…”
Section: Discussioncontrasting
confidence: 50%
“…The method may be applied in future studies with other BTX treatment protocols to quantify BTX-induced effects on muscle tissue and to investigate the spatial BTX distribution. A spatially limited extent of the BTX-induced effect, i.e., if the spread of BTX does not fully cover the zone of the motor end plates in the muscle (31), may help to explain a limited treatment effect on the gait and on the clinical scores of CP patients. Based on the MRI results, a revision of the applied treatment protocol regarding dose, dilution, or injections sites may be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BoNT-A can block acetylcholine release at cholinergic nerve endings of skeletal muscle. It results in temporary chemical denervation and reversible paralysis of striated muscles for a period of two to six months[ 14 , 15 ]. BoNT-A has proven effective in patients with spasticity in many upper motor neuron diseases[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…If after 3 months from the previous injection, there is a better functional situation than the one before the injection, it shows that BoNT has been effective, and, therefore, we can continue with this treatment. It has been shown that over the years, the effectiveness of repeated toxin injections is not usually lost; the main studies have been done in dystonia, but it has also been evidenced in spasticity, even in SCI [ 46 , 49 , 74 ].…”
Section: Treatment Of Spasticity In Spinal Cord Injury With Botulinum Toxinmentioning
confidence: 99%